2021
DOI: 10.1016/j.mtbio.2021.100127
|View full text |Cite
|
Sign up to set email alerts
|

Construction of multifunctional porcine acellular dermal matrix hydrogel blended with vancomycin for hemorrhage control, antibacterial action, and tissue repair in infected trauma wounds

Abstract: Prevention of bacterial infection and reduction of hemorrhage, the primary challenges posed by trauma before hospitalization, are essential steps in prolonging the patient's life until they have been transported to a trauma center. Extracellular matrix (ECM) hydrogel is a promising biocompatible material for accelerating wound closure. However, due to the lack of antibacterial properties, this hydrogel is difficult to be applied to acute contaminated wounds. This study formulates an injectable dermal extracell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(40 citation statements)
references
References 59 publications
(88 reference statements)
1
36
0
Order By: Relevance
“…Thus, cell-free extracellular matrix biomaterials can integrate into regenerative tissues without degrading or requiring removal [19,20]. Moreover, our previous study demonstrated that the skin extracellular matrix can promote skin healing [14].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, cell-free extracellular matrix biomaterials can integrate into regenerative tissues without degrading or requiring removal [19,20]. Moreover, our previous study demonstrated that the skin extracellular matrix can promote skin healing [14].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, hydrogel synthesis typically requires toxic crosslinking agents such as acrylic acid, polyvinyl alcohol, and glutaraldehyde, which may be cytotoxic and are not easily neutralized/eliminated in vivo [8,9,13]. To overcome these limitations, many researchers have developed biological drug carriers [14]. Reportedly, extracellular matrix materials (ECMs) exhibit good biocompatibility, can simulate the original cellular microenvironment, provide chemical and mechanical signals, guide cell adhesion, proliferation, and differentiation, and promote the repair and regeneration of homologous tissues [11,15].…”
Section: Introductionmentioning
confidence: 99%
“…The cytotoxicity of Np HM4 to HEK293 cells was assessed using the Cell Counting Kit-8 (CCK-8, K1018, APE×BIO, Technology LLC, Houston, TX, USA). As previously described [ 61 ], 6 × 10 4 cells were seeded into the wells of a 96-well microtiter plate and incubated at 37 °C for 48 h. Then, the supernatant medium was removed from each well, and 100 μL graded concentrations of DMEM containing Np HM4 were added (15, 30, 60, 90, and 180 μM, n = 3 for each concentration). The HEK293 cells cultured with DMEM (0 μM Np HM4) constituted the control group.…”
Section: Methodsmentioning
confidence: 99%
“…A biocompatible porcine acellular dermal matrix hydrogel blended with vancomycin has been developed for hemorrhage control, antibacterial action, and tissue repair in infected trauma wounds [ 276 ]. A patterned microstructural nanofibrous mats/gentamicin-loaded hydrogel composite scaffold has recently been proposed for skin tissue engineering [ 277 ].…”
Section: Antimicrobial Scaffolds For Tissue Engineeringmentioning
confidence: 99%